2021
DOI: 10.3390/v13061086
|View full text |Cite
|
Sign up to set email alerts
|

Severe Fever with Thrombocytopenia Syndrome Accompanied by Invasive Pulmonary Aspergillosis: An Autopsy Case

Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging tickborne infectious disease in China, Korea, and Japan caused by the SFTS virus (SFTSV). SFTS has a high mortality rate due to multiorgan failure. Recently, there are several reports on SFTS patients with mycosis. Here, we report a middle-aged Japanese SFTS patient with invasive pulmonary aspergillosis (IPA) revealed by an autopsy. A 61-year-old man with hypertension working in forestry was bitten by a tick and developed fever, diarrhea, and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…A survey by the Ministry of the Environment reported that the habitat area of Japanese deer and wild boars was mainly West Japan, although the area had been spreading northward every year [ 17 , 18 , 19 , 20 ]. A previous study concluded that wildlife habitat area changes also accelerated the spread of infection of Japanese spotted fever and scrub typhus, both of which are related to ticks [ 21 , 22 , 23 ]. The spread of the habitat area of the wild animals may also be associated with the distribution of the ticks carrying the SFTS virus and the differences between regions in terms of case prevalence; therefore, the spread of infection should be studied in the future.…”
Section: Discussionmentioning
confidence: 99%
“…A survey by the Ministry of the Environment reported that the habitat area of Japanese deer and wild boars was mainly West Japan, although the area had been spreading northward every year [ 17 , 18 , 19 , 20 ]. A previous study concluded that wildlife habitat area changes also accelerated the spread of infection of Japanese spotted fever and scrub typhus, both of which are related to ticks [ 21 , 22 , 23 ]. The spread of the habitat area of the wild animals may also be associated with the distribution of the ticks carrying the SFTS virus and the differences between regions in terms of case prevalence; therefore, the spread of infection should be studied in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, 35% patients with SFTS had bleeding symptoms ( Li H. et al., 2018 ) and severe cases were generally expired from systemic bleeding caused by disseminated intravascular coagulation ( Gai Z. T. et al., 2012 ). Gross pathological findings in patients with fatal SFTSV reported the subcutaneous hemorrhage in multiple sites, including anterior chest, neck, elbow, groin area, abdomen, and limbs ( Hiraki et al., 2014 ; Uehara et al., 2016 ; Kaneko et al., 2018 ; Iwao et al., 2021 ), also reported hemorrhage in the gastrointestinal tract and lungs ( Hiraki et al., 2014 ; Uehara et al., 2016 ; Kaneko et al., 2018 ; Iwao et al., 2021 ), as well as bilateral kidney swelling with subepithelial hemorrhage in the renal pelvis ( Takahashi et al., 2014 ). Coagulation dysfunction caused by platelet depletion was a risk factor for bleeding.…”
Section: Host Immune Responsementioning
confidence: 99%
“…Similarly, the significantly increased serum IP-10 levels were also found in patients with pneumonia at the acute phase of SFTSV infection when compared with those of patients with SFTS ( Deng et al., 2012 ), thus allowing for the speculation that IP-10 might play a role in the pathogenesis of SFTS-related lung injury. Furthermore, the autopsy studies of SFTS cases reported increased lung weight, alveolar hemorrhage, pulmonary edema, and diffuse alveolar injury ( Hiraki et al., 2014 ; Uehara et al., 2016 ; Kaneko et al., 2018 ; Iwao et al., 2021 ), indicating acute lung injury. SFTSV nucleoprotein antigen-positive atypical lymphoid cells were also detected in the lung ( Hiraki et al., 2014 ; Li S. et al., 2018 ).…”
Section: Host Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…The general population is susceptible; therefore, its epidemic area tends to expand following initial infection [ 5 ]. Thousands of incidents of SFTS have been reported in more than 16 provinces and cities in China [ 9 ] as well as in the Republic of Korea [ 10 ], Japan [ 11 ] and the USA [ 12 ].…”
Section: Introductionmentioning
confidence: 99%